Is sleep apnea truly associated with hearing loss? A nationwide, population-based study with STOP-BANG questionnaire - Lee, Jeon Mi; Lee, Hyun Jin (Frontiers in Public Health, 2023)
Objectives We aimed to investigate the effect of obstructive sleep apnea (OSA) on hearing ability. Methods We retrospectively reviewed the population-based survey data collected by the Korean National Health and Nutrition Examination Survey between January 1, 2019 and December 31, 2020. The data included 3,575 participants who completed the STOP-BANG questionnaire (SBQ) and pure-tone audiometry. OSA risk was assessed using the SBQ, and the hearing level was compared between the risk groups. Results Among the 3,575 participants, 2,152 (60.2%), 891 (24.9%), and 532 (14.9%) were classified as being low, intermediate, and high risk, respectively. The intermediate- and high-risk groups showed significantly worse hearing levels than the low-risk group. When age and sex were adjusted, the hearing level did not differ between the risk groups. Conclusion The study found that the presence of OSA minimally affected hearing level. Because hearing loss due to hypoxic damage develops over a long period of time, further research on the association between the duration of OSA, rather than the presence or severity of OSA, and hearing loss is needed.